41.2: A high‐accuracy DeMura algorithm based on sub‐pixel registration. (4th October 2019) - Yuan, Jie Yu; Feng, Xiao Fan; Zheng, Zeng Qiang; Zhang, Sheng Sen; Ma, Er Wei; Tang, Fei; Wu, Hong Jun
Abstract : In the production of display panel, due to the inadequate control of processing technology or insufficient technology, there will be various mura defects in the production of display panel, which seriously affects the economic benefits of manufacturers. In order to repair such mura defects and improve the economic benefits of display manufacturers, DeMura technology came into being. Most of the existing DeMura technologies are based on the virtual focus state of the camera. This paper proposes a DeMura technology based on high‐precision sub‐pixel location and brightness extraction in the precise focus state of the camera.